1998
DOI: 10.1136/emj.15.4.231
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to "brutacaine": a comparison of low dose intramuscular ketamine with intranasal midazolam in children before suturing.

Abstract: Objective-To compare the use oflow dose intramuscular ketamine with high dose intranasal midazolam in children before suturing. Methods-Altogether 102 children with simple wounds between 1 and 7 years old were allocated to the two study groups. Results-Two children were excluded from the study because of deviation from the agreed protocol. The 50 children in the ketamine group were less likely to cry or need to be restrained during the procedure than those in the midazolam group (p<0.0l).The median oxygen satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…It appears to be a separate entity from the ketaminespecific hallucinatory reactions 30 because it occurs at a similar frequency as with midazolam alone. 16,20,102 A recent study demonstrated that recovery agitation is not clinically significant in children. 30 Physicians graded ketamine recovery agitation using a 100-mm visual analog scale, with the median rating being 5 mm, low enough to lack clinical significance.…”
Section: Potential Adverse Effectsmentioning
confidence: 97%
“…It appears to be a separate entity from the ketaminespecific hallucinatory reactions 30 because it occurs at a similar frequency as with midazolam alone. 16,20,102 A recent study demonstrated that recovery agitation is not clinically significant in children. 30 Physicians graded ketamine recovery agitation using a 100-mm visual analog scale, with the median rating being 5 mm, low enough to lack clinical significance.…”
Section: Potential Adverse Effectsmentioning
confidence: 97%
“…The optimal oral dosing for ketamine that provides appropriate sedation with minimal or no adverse effects has not been determined yet. Common known adverse effects of ketamine include vomiting, transient ataxia and drowsiness 1013. Oxygen desaturation is a rare complication described only with intravenous or intramuscular delivery 12.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal transmucosal administration of drugs entails injection of a liquid vehicle into a child's nostril, a procedure most children resist vehemently. [16][17][18] Intramuscular administration of medications is more reliable than either oral or rectal routes, but it still presents a titration problem. Physical obstacles may be considerable with this route if a second dose is required in a developmentally or behaviorally challenged child beyond the first decade of life.…”
Section: Patient Assessmentmentioning
confidence: 99%